2022
DOI: 10.1111/1746-692x.12366
|View full text |Cite
|
Sign up to set email alerts
|

What Does Ecological Farming Mean for Farm Labour?

Abstract: Summary Ecological farming, such as organic and low‐input farming, is gaining popularity in the public discourse. One question is how this type of farming may impact farm labour from a socio‐economic point of view. The article first discusses how low‐input farming practices (i.e. with lower reliance on inputs derived from fossil fuels) may affect the economic returns to labour, measured as the farm’s revenue per hour of labour input, on data from the Farm Accountancy Data Network (FADN) in 2004‐‐2015 for four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It was not possible to assess the impacts on producer incomes because it was not possible to calibrate production costs for both the initial situation with conventional farm practices and the final situation with agro-ecological farm practices. On this point, it is worth noting that there is no consensus on the profitability of agro-ecological vs. conventional farming 36 , with inconsistent results between, for example, on the one hand van der Ploeg et al 37 , who concluded that agro-ecology in the EU would be more profitable than conventional agriculture (on the basis of several case studies), and on the other hand Davidova et al 38 , who reached an opposite conclusion with lower labor returns in low-input farming systems (on the basis of FADN-Farm Accountancy Data Network-samples for different EU countries). Of course, these assessments were based on observed prices and not simulated prices.…”
Section: Short Names Of Scenarios Assumptionsmentioning
confidence: 99%
“…It was not possible to assess the impacts on producer incomes because it was not possible to calibrate production costs for both the initial situation with conventional farm practices and the final situation with agro-ecological farm practices. On this point, it is worth noting that there is no consensus on the profitability of agro-ecological vs. conventional farming 36 , with inconsistent results between, for example, on the one hand van der Ploeg et al 37 , who concluded that agro-ecology in the EU would be more profitable than conventional agriculture (on the basis of several case studies), and on the other hand Davidova et al 38 , who reached an opposite conclusion with lower labor returns in low-input farming systems (on the basis of FADN-Farm Accountancy Data Network-samples for different EU countries). Of course, these assessments were based on observed prices and not simulated prices.…”
Section: Short Names Of Scenarios Assumptionsmentioning
confidence: 99%
“…Considering these limitations, our degree of ecologisation measure is primarily related to the 'low-input' farming approach, which is also referred to as 'low intensity' or 'reduced input' farming, as it reduces the pressures that agriculture places on the environment, including greenhouse gas emissions and water pollution, through reduced reliance on external inputs derived from fossil fuels (Davidova et al, 2022).…”
Section: Datamentioning
confidence: 99%
“…All managers of agroforestry systems with lower labour demand than monoculture references stated the explicit objective to keep labour demand moderate to low, which is a common strategy amongst many agroforestry farmers around the world, even if it is associated with low productivity (Adimassu et al, 2015;Fujisawa et al, 2020;Scudder et al, 2022;Tilden et al, 2023). From a profitability point of view, this can be beneficial as labour costs are often the largest expense and incremental productivity gains in response to increased labour inputs do not always pay off (Davidova et al, 2022;Esche et al, 2022;Scudder et al, 2022). As multistrata systems can nevertheless be expected to provide more ecosystem services than simplified monocultures (Santos et al, 2019;, these low-labour multistrata agroforestry systems are showcasing a viable approach to multifunctional land management.…”
Section: Agroforestry Complexity and Labour Demandmentioning
confidence: 99%